A continuous droplet electroporation system for high throughput processing. Issue 23 (23rd October 2018) - Yoo, Byeong Sun; Im, Do Jin; Ahn, Myung Mo; Park, Sung Jin; Kim, Yeong Hun; Um, Tae Woong; Kang, In Seok
Abstract : A continuous droplet electroporation (EP) system capable of handling a billion cells has been proposed and demonstrated using a proof-of-concept prototype design. Abstract : A continuous droplet electroporation (EP) system capable of handling a billion cells has been proposed and demonstrated using a proof-of-concept prototype design. Numerical simulations were conducted to design the new system and to compare the continuous droplet EP system with the previous single droplet EP system. Through parametric studies on the applied voltage and flow rate, a much higher cyan fluorescent protein transgene expression efficiency (38.8 ± 8.9%) was accomplished over that of the previous single droplet EP system. A parallel continuous droplet EP system is also demonstrated by introducing additional electrode pairs into the continuous droplet EP system to achieve ultrahigh throughput. Finally, the significance and meaning of the present work and future development direction have been discussed.